INTEGRASI REMEDIASI KESULITAN BELAJAR MENGGUNAKAN MODEL CORE BERBANTUAN BOOKLET TENTANG GETARAN GELOMBANG DI SMP - Ariza Fitriani Safira; Haratua Tiur Maria S; Syukran Mursyid (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2020)
This research aims to examine the effectiveness of the integrated remediation using booklet-assisted CORE leraning model to reduce students' learning difficulties about vibrations and waves at SMP Negeri 2 Pontianak. The research design is One-Group Pretest-Posttest Design with 27 students in class VIII C as samples using the intact group technique. The instruments are two-tiered multiple choice tests to analyze students’ learning difficulties related to concepts and essay tests to analyze students’ learning difficulties related to errors in solving problems. Based on the results, it is found that: (1) Students’ total misconceptions decreasing by 84.2%. (2) There is a significant conceptual change in all test items. (3) All students’ total errors in solving questions decreased by 78.32% (4) There are significant difference between the number of students' initial and final mistakes. (5) The percentage of all students’ learning difficulties decreased by 78.91%. (6) The remediation integration using CORE model assisted by a booklet has a high effectiveness to reduce students’ learning difficulties. The result of this study is expected to be a consideration for teachers in designing learning difficulties’ remediation activities for students, especially about vibrations and waves.